(untitled) (Afaq Lughawiyyah, 2024)
The study of musical beautifications in a poem is one of the musts sweated and very nice studies of rhyme because of its dipping in showing the phonological sense and rhythmicity inspiration. Also, in explaining each phenomenon of external music along with its consonants and vowels among others as it indeed proves the poet’s expertise in his beautiful exchanging which is suitable to the purpose of poem. In view of the above this paper is prepared in order to show out the hidden secret of musical beauties in the poem titled: “La Nabtagi Fikum Siwal Khairat” for the poet Dr. Abubakar Adamu Masama concentrating on the following phonological and rhyming phenomenon: Rhyming letter, Rhyming vowel, attaching letter unconditional utilization by study and analysis.